Handbook of Eating Disorders / Theory,Treatment and Research - Dare Chris; Garfinkel Paul E; Szmucler George; Treasure Janet (John Wiley & Sons, 1998)
This volume provides an up-to-date review of anorexia nervosa and bulimia nervosa. Foreword, Preface, Concepts and Definitions, Anorexia Nervosa Through Time, The Essence of Anorexia Nervosa: Comment on Gerald Russell's ''Anorexia Nervosa Through Time'', Something New Under the Sun: Comments on Gerald Russell's ''Anorexia Nervosa Through Time'', Current Concepts and Definitions, Etiology, Genetic Factors in Eating Disorders, Starvation Models and Eating Disorders, A Physiology of Starvation that Sustains Eating Disorders, Psychodynamic Models of Eating Disorders, Family Models of Eating Disorders, Consequences and Maintaining Factors, Medical Complications of Chronic Anorexia Nervosa, Treatments, Cognitive Therapy, Family Therapy, Physical Treatments, Prevention, Acknowledgements of the Contribution of G.F.M. Russell, Index.